Application of Self-Talk Techniques to Enhance Self-Confidence among University Football Athletes - Farhanul Insan Zinda; Komarudin Komarudin; Mochamad Yamin Saputra; Geraldi Novian; Siti Nursaba (ACTIVE: Journal of Physical Education, Sport, Health and Recreation, 2026)
In the sport of football, athletes often experience a decrease in self-confidence when facing match pressure or after making mistakes, such as failing in passing, losing the ball, or failing to score a goal. This condition can lead to a decline in the athlete's performance and hesitation in making decisions on the field. One psychological technique to overcome this problem is the self-talk technique, which is an individual's ability to give instructions or suggestions to themselves. This study aims to examine the effect of applying the self-talk technique in increasing the self-confidence of football athletes. An experimental method with a pretest-posttest design was used in this study involving 25 football athletes from the Indonesia University of Education. The instrument used was a self-confidence questionnaire administered before and after the self-talk treatment over one week. Data analysis was conducted using statistical tests with the help of SPSS. The study results showed an increase in the athletes' self-confidence levels after being given self-talk treatment, as indicated by the difference in scores between the pretest and posttest. This study concluded that the self-talk technique has an effect on improving the self-confidence of football athletes.training can be systematically designed to foster optimal athletic mindsets.